The Effects of Organizational Citizenship Behavior: A Study in a Private School in Sharjah - Askar, Zeina (2018)
Today modern education demands educators and educational organizations to innovate new methods to increase school effectivity. Theoretical findings shows teachers perform extrarole activities known as Organizational Citizenship behavior (OCB) with no pay or recognition. School managers found OCB as a new method to increase school effectivity with high dependency on OCB teachers. This study aims to understand OCB and its effects on teachers in a Sharjah private school in the UAE. The study used a mixed method approach running two questionnaires to analyze results reported by 122 participants. Both qualitative and quantitative approaches were used to collect data using 20 items from the 49-item questionnaire developed by Watson and Tellegen (1985). This method conceptualizes the concept of OCB and its effect on teacher in the school, through importance and participant self-reported feelings. The study shows that OCB is important to teachers and “Sportsmanship” was the most important OCB dimension; employees tolerate certain circumstances due to the organizations decisions without complaining. The positive effectivity of OCB analysis shows “Courtesy” was the most important dimension of OCB, and feeling “Active” was most expressed. Indicating that teachers resolve and avoid work-related problems. The overall positive implications encourage further research to understand OCB in UAE schools, with a focus as to what motivates teachers to perform OCB.